Analysis of solder joint reliability of high power LEDs by transient thermal testing and transient finite element simulations. Issue 12 (December 2015) - Elger, Gordon; Kandaswamy, Shri Vishnu; Liu, E.; Hanss, Alexander; Schmid, Maximilian; Derix, Robert; Conti, Fosca
Abstract: An innovative sensitive test method is developed to detect solder joint cracking for high power LED packages. The method is based on transient thermal analysis and can fully replace the still dominating light-on test. For experimental application of the model, test groups of LED packages were soldered with two different lead free solders (SnAgCu305 and Innolot FL-640) on Aluminum Insulated Metal Substrate (Al-IMS) and exposed to temperature cycles. Transient thermal measurements were performed directly after assembly and after specific cycle numbers. After data processing the increase of the relative thermal resistance between the initial signal at "0" cycles and " n " cycles is obtained and correlated with cracks in the solder joint by cross sections. Based on the CAD and material data of the LED package a finite element (FE) model is set up. The time-resolved temperature curves are properly reproduced by transient thermal simulation. The measured "0" cycle curves are fitted using the FE model by adjusting a few material parameters within their allowed tolerance range. A parameter sensitivity analysis is performed. The impact of a crack in the solder joint between package and printed circuit board (PCB) on the time resolved temperature curve is simulated. The simulated crack propagates from the corner of the package to its center. The experimental measured curves are reproduced. Based on the simulation a failure criteria is defined, representing a crack length between 20% and 30% of the solder joint area, and Weibull curves are calculated. A higher creep resistance for the test group soldered with Innolot FL-640 compared to the test group soldered with SAC305 is observed.